????? - ???????? ??????? ?? ??? ????????? ???????????? - Vaxobov Alisher , Khatamova Hamida Komiljonovna, Solieva Madinahon Botirovna , Dexqonova Shakhnoza Yulbarsovna (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In order to ensure food security of the population of the country, it is necessary to increase the productivity of fruits, vegetables, potatoes, to organize high-quality seed production and to introduce new technologies. It is expedient to selectively introduce nutritious, vitamin-rich, high-yielding rare plants that are valuable for consumption in vegetable growing and to plant them on a large scale by organizing seed production for farms and landowners through specialists in the field. In this article, the authors tried to give recommendations on how to grow an okra plant, which is a unique vegetable crop, and get a higher yield.